A Loose Affiliation of Alleluias: Tracing Genealogies of Technique and Power in Creative Practice - Oram, Celeste; GoGwilt, Keir (Current Musicology, 2021)
This article is written from our perspectives as a performer and a composer, focusing on our violin concerto, “a loose affiliation of alleluias”, which we created and premiered in 2019. Making this concerto was an exercise in excavating the material histories that guide our creative practice. Our purpose in doing so was to work towards a clear and necessarily complex appraisal of how our current practices are motivated by, and reproduce, historically-determined knowledge, authority, and cultural attitudes. We think through our own reproductions of historical knowledge via Ben Spatz’s exegesis of “technique”, and via Edward Said’s notion of “affiliations” as the networks which build up cultural associations and cultural authority. With this theoretical frame, we contextualize some of the musical techniques and tropes engaged in our concerto—for instance polyphony, ornamentation, and the concerto soloist as heroic subject. We contextualize our reflections next to critical positions staked circumscribed by what Ben Piekut calls “elite avantgardism”—an analytical category which we see ourselves as operating within. We discuss, for instance, the critical gestures of musical modernism which (per Adorno’s analysis) conspicuously arrest and negate historical musical grammars and logics – and yet continue to reproduce its structuring values. In our concluding statements we gesture towards some of the pedagogical implications of this work, considering how creative practice can be leveraged to re-appraise the histories shaping our practices of composition, improvisation, and performance.